Digital cultural transmission: TikTok as a medium for the preservation and learning of Riau Malay Dance in informal communities - Syefriani Syefriani; Muhammad Fazli Taib Saearani (Pascasarjana Institut Seni Indonesia Surakarta, 2025)
Digital transformation has reshaped the ways in which culture is transmitted, including Riau Malay Dance, which is currently facing a decline in interest among younger generations and the dominance of popular culture. At the same time, social media platforms such as TikTok have developed into informal learning spaces that are closely integrated with the everyday lives of adolescents. This study emerges from the gap between, on the one hand, the threat of fading interest in Riau Malay Dance and, on the other hand, the limited number of studies that specifically examine TikTok as a medium for the preservation and learning of traditional dance in informal community settings. This research employs a qualitative method with a digital ethnography approach through participatory observation, in-depth interviews, and documentation of TikTok content related to Riau Malay Dance. The findings indicate that TikTok functions as a participatory learning space that facilitates processes of observation, imitation, and movement modeling; fosters intergenerational learning communities; and archives dance in digital format through tutorial content, performances, and creative reinterpretations. However, several challenges arise, including the commodification of culture, superficial cultural understanding, gaps in digital literacy, and algorithmic bias toward popular content. Scientifically, this study offers a renewed understanding of digital cultural transmission and underscores the importance of digital cultural literacy strategies and content standards to balance media innovation with the authenticity of Riau Malay Dance in the global era.